Acute metabolic decompensation after liver transplant in a patient with maple syrup urine disease - Shao Ching Tu; Marium Khan; Katie Wolfe; Sakil S. Kulkarni; Elizabeth Toolan; Dorothy K. Grange (JIMD Reports)
Abstract Maple syrup urine disease (MSUD) is an inborn error of metabolism characterized by the accumulation of branched‐chain amino acids (leucine, isoleucine, and valine) caused by a defect in the branched‐chain alpha‐keto acid dehydrogenase complex. Liver transplant is an effective therapy for MSUD, and patients can usually tolerate a regular diet after transplant without symptomatic metabolic decompensation. Most post‐transplant patients do not follow a sick‐day diet. We report a case of a 7‐year‐old male with MSUD Type IA, status post‐liver transplant at 2 years of age, who presented with profound encephalopathy following poor oral intake and vomiting for 3 days. Broad laboratory workup was significant for hyperleucinosis and an unrevealing infectious workup. We conducted a review of eight post‐liver transplant MSUD patients followed at Washington University in St. Louis. The review revealed that plasma amino acids were generally not checked during intercurrent illnesses in this patient cohort. While most of our patients have not had documented encephalopathy, one of the patients with epilepsy had a seizure during a gastrointestinal illness. Based on the review of the literature and from our center's experience, acute metabolic decompensation with intercurrent illnesses in MSUD patients after liver transplant appears to be rare. This case report raises awareness that patients with MSUD are still at risk of developing metabolic crisis post‐liver transplant and provides additional insight into the risk factors associated with metabolic decompensation in this patient cohort.